Optimal planning of wind farms using wera model integrated with GIS - DEVANAND U. GORATE; Dr. Sathyajith Mathew (Tavanur 2006 Department of Farm Power Machinery and Energy)
Optimal planning of wind farms using wera model integrated with GIS
Optimal planning of wind farms using wera model integrated with GIS